Manuskrip keagamaan dan Islamisasi di Buton abad 14-19 - Muhammad Abdullah, (Universiti Kebangsaan Malaysia, 2007)
Manuscripts from Buton written in the 18th century describe the process of Islamisation that took place there. Historically, Islam came to Southeast Sulawesi in the 17th century in waves. Firstly, it was formally adopted by the kingdom of La Kilaponto. Secondly, Islamic values were implemented during the time of the kingdom of Dayanu Ihsanuddin through the Martabat Tujuh Constitution. Thirdly, Islamic thought and laws were propagated during the 5th Buton Kingdom by the religious teacher Haji Abdul Ghani. Finally, an Islamic state was formed in Buton in the 19th century, which practiced syariah laws